Capital Budgeting Analysis to Enhance Bank Performance and Stock Price (Case Study of Bank Tabungan Negara Period 2010-2014) (The Indonesian Journal of Business Administration, 2015)
Abstract. Bank Tabungan Negara (BTN) is a state-owned bank focusing its business on housing finance. In the last five years, the BTN stock has been experiencing a decline in its price. The decline of the BTN stock price is in accordance with the poor performance of the bank in comparison with that of other banks having core capitals in the same category (the BUKU 3). To increase BTN’s financial performance as well as its stock price, it argued in this final project that BTN needs additional funds to expand its business.  The objective of this final project is to propose a financial planning that can be used by BTN to gain the additional funds for improving its financial performance as well as to achieve its targeted stock price. External and Internal analyses are conducted to uncover business problems faced by BTN. The external analysis was done using the PESTEL analysis, and the internal analysis was performed using the Ratio analysis and Economic Value Added (EVA) analysis. The Discounted Method of Economic Value Added is used to attain the projection of the BTN’s stock price for the next three years. The Price Earning Ratio (PER) methodis used to obtain the BTN’s targeted stock price. From the analyses, it is found that BTN needs to gain five trillions Indonesia Rupiah as the additional fund to improve its financial performance as well as its stock price. There are three ways that are recommended in this final project for BTN to get the additional fund, which are by issuing right issue, issuing bond, and gaining loan from its stockholders. The amount of the additional fund that can be obtained from each way is determined by considering the BTN historical right issue and bond issue, as well as BTN’s plan in 2015. In a case BTN conducts the right issue, it is recommended for (1) the BTN current stockholders to exercise their rights and (2) potential investors to buy the BTN rights that are traded in the market to get a high capital gain.Key word: capital budgeting, PESTEL analysis, ratio analysis, economic value added, financial performance, stock price